Sugar Hill Project: Harlem, New York - David Adjaye (Oz, 2015)
Sugar Hill is a new mixed-use development in Harlem’s historic Sugar Hill district that features affordable housing, a children’s museum, preschool, non-profit offices, and underground parking. Initiated by non-profit developer of supportive housing, Broadway Housing Communities (BHC), and generated by a tight budget as well as the exacting parameters of the site, the concept challenges the traditional typology of low cost housing and reflects Adjaye Associates’ commitment to a wider urban and cultural responsibility.